In-Hospital Mortality and Its Predictors among Hospitalized Diabetes Patients: A Prospective Observational Study - Dereje Eyob Tediso; Fekede Bekele Daba; Teshale Ayele Mega (International Journal of Clinical Practice)
Background. Diabetes mellitus (DM) is one of the leading health emergencies of the 21st century and among the top ten causes of death among adults globally in 2017. Although Ethiopia has been victimized by the growing prevalence of DM, data regarding in-hospital mortality among admitted diabetic patients in Ethiopia, specifically in Jimma Medical Center (JMC), are lacking. Objective. The aim of the study is to assess in-hospital mortality and its predictors among DM patients admitted to Jimma Medical Center. Methods. A hospital-based prospective observational study was employed involving 120 diabetes patients admitted to JMC from October 01, 2020, to June 30, 2021. Data were collected on variables related to the patient, disease, medication, and clinical outcomes. Data were entered into Epidata version 4.6.0.4 for cleaning and exported to SPSS version 23.0 for analysis. Kaplan–Mayer and cox-regression analyses were used to compare the survival experience and to determine the predictors of clinical outcomes, respectively. Hazard ratio with its two-sided p value <0.05 was considered to declare the statistical significance. Result. Of 120 DM patients, 81 (67.5%) of them were males. The in-hospital mortality was 13.34% (16/120). Rural residence (AHR: 3.46; 95% CI (1.12, 9.81)), age (AHR: 1.03; 95% CI: (1.001, 1.059)), admission with diabetic ketoacidosis (AHR: 5.01; 95% CI (1.12, 21.88)), and multiple comorbidities: five comorbidities (AHR: 9.65; 95% CI (1.07, 19.59)) and six comorbidities (AHR: 14.02; 95% CI (1.74, 21.05)) were independently associated with in-hospital mortality. On the other hand, exposure to nonantidiabetic medications decreased the hazard of mortality by 86.5% (AHR: 0.135; 95% CI (0.04, 0.457)). Conclusion. This study showed the rate of in-hospital mortality was noticeably high. The study showed that rural residence, age, DKA, and having comorbidities (five and six) were the statistically significant predictors of in-hospital mortality. In contrast, the use of nonantidiabetic medications such as statins, ASA, and other antihypertensive agents before admission remained protective. Thus, proper strategies have to be devised to improve in-hospital mortality among admitted DM patients.